2015
DOI: 10.1063/1.4921072
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cu2+-Aβ complexes from computational approaches

Abstract: Amyloid plaques formation and oxidative stress are two key events in the pathology of the Alzheimer disease (AD), in which metal cations have been shown to play an important role. In particular, the interaction of the redox active Cu2+ metal cation with Aβ has been found to interfere in amyloid aggregation and to lead to reactive oxygen species (ROS). A detailed knowledge of the electronic and molecular structure of Cu2+-Aβ complexes is thus important to get a better understanding of the role of these complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 66 publications
(94 reference statements)
0
6
0
1
Order By: Relevance
“…BLYP is also tested here because it is the functional used in many previous CPMD/BOMD simulations of solvated copper ions (see below). MPWB1K, a meta-GGA functional, is tested because a recent study 52 found it to work well for several copper complexes. To obtain longer DFT/MM simulations, a small basis that contains the Hay−Wadt effective core potential (Lanl2dz 53 ) for copper and 6-31G(d) for other elements is used; gas phase calculations for copper−water complexes (Tables 1 and 2 and Supporting Information) indicate that this basis set leads to good geometries in comparison to calculations using aug-cc-pVTZ.…”
Section: Methodsmentioning
confidence: 99%
“…BLYP is also tested here because it is the functional used in many previous CPMD/BOMD simulations of solvated copper ions (see below). MPWB1K, a meta-GGA functional, is tested because a recent study 52 found it to work well for several copper complexes. To obtain longer DFT/MM simulations, a small basis that contains the Hay−Wadt effective core potential (Lanl2dz 53 ) for copper and 6-31G(d) for other elements is used; gas phase calculations for copper−water complexes (Tables 1 and 2 and Supporting Information) indicate that this basis set leads to good geometries in comparison to calculations using aug-cc-pVTZ.…”
Section: Methodsmentioning
confidence: 99%
“…DFT and ab initio methods have been used to investigate copper-Aβ interactions, but their computational expense typically requires the use of model systems such as Cu–Aβ 1–16 or smaller. , In addition, hybrid quantum mechanics/molecular mechanics (QM/MM) was applied to Cu–Aβ 1–16 to model energetics and redox potentials of different Cu-binding modes. , QM/MM combined with homology modeling was carried out by Ali-Torres et al to probe the Cu­(II)–Aβ 1–16 coordination sphere. The 3N1O model was considered with His6, His13 and His14 as nitrogen ligands, including δ and ε binding modes, with a range of potential residues for the oxygen ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Structural details for naturally occurring metals such as Cu and Zn have been elucidated through a wide range of experimental [ 14 ][ 15 ] and simulation techniques,[ 16 ][ 17 ][ 18 ][ 19 ] but the equivalent for Pt is scarcer. Ma et al used HPLC, ESI-MS and NMR spectroscopy to examine the binding of Pt II -phenanthroline to Aβ, suggesting that binding to His6 and His14 predominates and that π-stacking to aromatic residues Phe4, Tyr10 and His13 may also play a role.…”
Section: Introductionmentioning
confidence: 99%